2017
DOI: 10.1016/j.jses.2017.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Publication rates of podium presentations at the American Shoulder and Elbow Surgeons annual open versus closed meetings 2008 to 2012

Abstract: AimThe purpose of this study was to analyze the publication rate for abstracts presented at podium presentations from the American Shoulder and Elbow Surgeons (ASES) annual open and closed meetings from 2008 to 2012.Materials and methodsAbstracts accepted as podium presentations for the open and closed meetings from 2008 through 2012 were followed. A search was performed using Google Scholar and PubMed for all published manuscripts. This analysis looks at abstracts categorized based on annual meeting (open ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
13
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 16 publications
5
13
0
4
Order By: Relevance
“…The publication rates in this analysis are comparable to recently published rates of other orthopaedic society podium presentations, from AOSSM and ASES among others. 4,6 The POSNA abstracts include a consistent level of evidence assessment, 8 allowing comparison of publication research quality between podium and poster presentations. Our findings are consistent with the analysis done by Gowd et al 6 that AOSSM abstract podium presentations are significantly more likely to be published in higher-impact factor journals and be cited more frequently.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The publication rates in this analysis are comparable to recently published rates of other orthopaedic society podium presentations, from AOSSM and ASES among others. 4,6 The POSNA abstracts include a consistent level of evidence assessment, 8 allowing comparison of publication research quality between podium and poster presentations. Our findings are consistent with the analysis done by Gowd et al 6 that AOSSM abstract podium presentations are significantly more likely to be published in higher-impact factor journals and be cited more frequently.…”
Section: Discussionmentioning
confidence: 99%
“…These rates are in line with publication rates for abstracts presented at other surgical subspecialty conferences, as well as subspeciality orthopaedic conferences. [2][3][4][5] The 2008 to 2012 American Shoulder and Elbow Surgeons (ASES) annual meetings had a 61% publication rate for podium presentations. 4 The only factor impacting publication of podium or poster presentations from 2011 to 2015 American Orthopaedic Society for Sports Medicine (AOSSM) conferences was number of co-authors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…13 Further limitations include the inability to obtain data with regard to number of abstracts submitted each year, although we can extrapolate from other literature that demonstrates a decreasing abstract acceptance rate over time in the general orthopaedic literature. 3,4,7,9,13…”
Section: Discussionmentioning
confidence: 99%
“…13 Prior studies have demonstrated the rate of publication for abstracts presented at other orthopaedic conferences to range from 40.1% to 61%. 4,5,9,10,22 Additionally, podium presentations have been found to be more impactful than posters, based on a higher publication rate. Sprague et al 19 reported that the most common self-reported barriers to publication 5 years after presentation at the American Academy of Orthopaedic Surgeons (AAOS) Annual Meeting in 1996 were lack of time to prepare a manuscript, ongoing recruitment for studies, and disputes with coauthors.…”
mentioning
confidence: 99%